2021
DOI: 10.51791/njap.v36i1.1037
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and influence of spur gene on six metric traits in Nigeria Local Chicken

Abstract: A study was collected in two local government arears of Oyo state,Nigerian, an adult, free-ranging indigenous chiken on the incidence and possible influence of the spur gene (sl) on the body weight and five other matric traits: Body length (BL), wing length (WL), shank length (SL), shank thickness (ST) and breast girth (BG) which are indicative of the body size and growth 486 (37.15%) of the 1039 sampled local fowls were sparrowed and the gene frequency was estimated to 0.61. the calculated gene and genotype f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Spurred native chickens irrespective of sex had significantly (P< 0.05) higher body weight, shank length, thigh length, body girth, toe length and shank thickness than spurless native chickens in the study area. This observation agrees with the report of Egena et al (2011) but contradicts the result of Oguntunji and Ayorinde (2009) who reported non-significant (P> 0.05) higher mean values for body weight and linear body parameters of spurred native chickens over spurless native chickens of Nigeria. The higher performance of spurred native chickens over their spurrless counterparts observed in this study, irrespective of sex, could suggest that the presence of spur gene in a chicken may have a pronounced positive influence on its body weight and body linear measurements.…”
Section: Effect Of Spur Gene On Body Weight and Linear Body Measurementssupporting
confidence: 83%
See 3 more Smart Citations
“…Spurred native chickens irrespective of sex had significantly (P< 0.05) higher body weight, shank length, thigh length, body girth, toe length and shank thickness than spurless native chickens in the study area. This observation agrees with the report of Egena et al (2011) but contradicts the result of Oguntunji and Ayorinde (2009) who reported non-significant (P> 0.05) higher mean values for body weight and linear body parameters of spurred native chickens over spurless native chickens of Nigeria. The higher performance of spurred native chickens over their spurrless counterparts observed in this study, irrespective of sex, could suggest that the presence of spur gene in a chicken may have a pronounced positive influence on its body weight and body linear measurements.…”
Section: Effect Of Spur Gene On Body Weight and Linear Body Measurementssupporting
confidence: 83%
“…Results are similar to the reports of Egena et al, 2011, Momoh andKershima (2008) for Nigerian indigenous chickens, and Dossou (2005), Youssaou et al (2010) for indigenous chickens in Benin republic. However, some researchers (Fayeye et al, 2006;Oguntunji and Ayorinde, 2009) reported that Nigerian indigenous chicken males had non-significantly (P> 0.05) higher body weight and body linear measurements than their female counterparts. The observed differences in body weight and body linear measurements by different authors could be attributed to age of birds, nutritional and health status of birds at the time of sampling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, hens with removed ovaries all grew spurs ( Hutt, 1949 ). The sex-influenced nature of spur incidence is supported in other studies ( Fairfull and Gowe, 1986 ; Oguntunji and Ayorinde, 2009 ; Egena et al, 2011 ). The tail length, which is made up of feathers for balance while walking and a steering mechanism while in flight, was mainly medium across the regions.…”
Section: Discussionsupporting
confidence: 63%